Treasure from garden: Bioactive compounds of buckwheat - Huda, Md. Nurul; Lu, Shuai; Jahan, Tanzim; Ding, Mengqi; Jha, Rintu; Zhang, Kaixuan; Zhang, Wei; Georgiev, Milen I.; Park, Sang Un; Zhou, Meiliang (Food chemistry, 2021)
•An extensive review on diverse bioactive components of buckwheat.•Versatile beneficial phytochemicals are abundant in buckwheat.•Buckwheat has a wide range of pharmacological and beneficial health effects.•Huge research scope on Fagopyrum cymosum to identify the beneficial phytochemicals. Buckwheat is a gluten-free crop under the family Polygonaceae abundant with beneficial phytochemicals that provide significant health benefits. It is cultivated and adapted in diverse ecological zones all over the world. Recently its popularity is expanding as a nutrient-rich healthy food with low-calories. The bioactive compounds in buckwheat are flavonoids (i.e., rutin, quercetin, orientin, isoorientin, vitexin, and isovitexin), fatty acids, polysaccharides, proteins, and amino acids, iminosugars, dietary fiber, fagopyrins, resistant starch, vitamins, and minerals. Buckwheat possesses high nutritional value due to these bioactive compounds. Additionally, several essential bioactive factors that have long been gaining interest because these compounds are beneficial for healing and preventing several human diseases. The present review demonstrates an overview of the recent researches regarding buckwheat phytochemicals and particularly focusing on the distinct function of bioactive components with their health benefits.